2017
DOI: 10.18632/oncotarget.20120
|View full text |Cite
|
Sign up to set email alerts
|

The use of neutrophil to lymphocyte ratio as a predictor for clinical outcomes in spontaneous intracerebral hemorrhage

Abstract: ObjectiveNeutrophil to lymphocyte ratio (NLR) is used as an independent predictor for clinical outcomes in cancers, cardiovascular disorders and ischemic stroke. The prognostic role of NLR in spontaneous intracerebral hemorrhage (sICH) is still controversial. The aim of this report is to conduct a meta-analysis to evaluate the prognostic significance NLR in patients with sICH.Materials and MethodsAll related articles were searched on PubMed, EMBASE, Cochrane Central Register of Controlled Trials followed the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Inflammation is considered a major player in the development of secondary brain injury after stroke (Qun et al, ; Ye et al, ). The neutrophil‐to‐lymphocyte ratio has been recognized as a simple and reliable inflammatory marker (Zahorec, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation is considered a major player in the development of secondary brain injury after stroke (Qun et al, ; Ye et al, ). The neutrophil‐to‐lymphocyte ratio has been recognized as a simple and reliable inflammatory marker (Zahorec, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our target is determining the best NLR predictors. The cutoff values for various diseases vary; for example, the symptomatic intracranial hemorrhage (sICH) has a value of 4.08–7.35 (Ye et al, ), and cardiovascular disease has a value of 3.5–7.6 (Bhat et al, ). In one of the articles we included, Malhotra et al () did not perform a regression analysis on the predictive value of NLR in patients with AIS, and we excluded it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that NLR1, NLR3, and NLR7 were not independently predictive of 3-month outcomes. A recent meta-analysis assessed the prognostic role of NLR in patients with sICH and concluded it is time-dependent, with values increasing over the first few days [45]. Conversely, Sun et al [24] have reported that NLR at admission is not associated with 3-month outcomes post-ICH, possibly due to a single NLR measurement on admission, different risk factors, heterogeneity, and regional disparity.…”
Section: Discussionmentioning
confidence: 99%
“…Blood leukocyte and neutrophil counts are conventional inflammatory markers. Recently, it is found that neutrophil to lymphocyte ratio (NLR) is a diverse functional prognosis predictor in some diseases, such as myocardial infarction, adult polymyositis and dermatomyositis, and spontaneous intracerebral hemorrhage [15][16][17]. NLR is related to immune dysregulation in patients with cirrhosis and is inexpensive to measure.…”
Section: Prognostic Biomarkers Of Survival Ratementioning
confidence: 99%